2011
DOI: 10.1160/th10-12-0810
|View full text |Cite
|
Sign up to set email alerts
|

Atorvastatin reduces thrombin generation and expression of tissue factor, P-selectin and GPIIIa on platelet-derived microparticles in patients with peripheral arterial occlusive disease

Abstract: We investigated the effects of statin treatment on platelet-derived microparticles (PMPs) and thrombin generation in atherothrombotic disease. Nineteen patients with peripheral arterial occlusive disease were randomised to eight weeks of treatment with atorvastatin or placebo in a cross-over fashion. Expression of GPIIIa (CD61), P-selectin (CD62P), tissue factor (TF, CD142) and phosphatidylserine (PS; annexin-V or lactadherin binding) was assessed on PMPs. Thrombin generation in vivo was assessed by measuremen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
70
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 92 publications
(76 citation statements)
references
References 32 publications
6
70
0
Order By: Relevance
“…Like their parental cells, PMPs are involved in hemostasis, maintenance of vascular health, and immunity. 3,6,21,23,29,30,42 Here, we report that PMPs have the capacity to prevent the differentiation of Tregs into IL-17-and IFN-g-producing cells, even in the presence of proinflammatory cytokines. The mechanism of action consists of rapid and selective P-selectin-dependent binding of PMPs to a specialized CCR6…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Like their parental cells, PMPs are involved in hemostasis, maintenance of vascular health, and immunity. 3,6,21,23,29,30,42 Here, we report that PMPs have the capacity to prevent the differentiation of Tregs into IL-17-and IFN-g-producing cells, even in the presence of proinflammatory cytokines. The mechanism of action consists of rapid and selective P-selectin-dependent binding of PMPs to a specialized CCR6…”
Section: Discussionmentioning
confidence: 95%
“…52,53 These megakaryocyte-derived microparticles are abundant in healthy individuals, 3 whereas PMPs, identified by the expression of platelet activation markers P-selectin and/or CD63, are only observed during disease. 29,42 This implies that although megakaryocyte-derived microparticles have a more systemic function, PMPs may act locally at sites of platelet activation and that each has its own distinct role in homeostasis.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, in patients with peripheral arterial occlusive disease, atorvastatin treatment reduced the expression of tissue factor, GPIIIa and P-selectin in platelet-derived microparticles thus inhibiting initiation of thrombin generation [79].…”
Section: Future Directionsmentioning
confidence: 99%
“…ETP is increased in obese children as young as six years of age [40] and hemostatic alterations can normalize after weight loss due to successful lifestyle intervention [41]. Patients with peripheral arterial occlusive disease treated for 8 weeks with atorvastatin showed a significant reduction of thrombin generation [42]. The mechanisms by which statins reduce thrombosis risk are unclear, but a recent review by researchers at the National Institutes of Health (NIH) confirmed that the anti-thrombotic effects of statins are likely related to their anti-inflammatory properties [43].…”
Section: Statins and Inflammatory Parametersmentioning
confidence: 99%